Limited Earthquake Interaction During a Geothermal Hydraulic Stimulation in Helsinki, Finland. Issue 9 (12th September 2022) - Kwiatek, Grzegorz; Martínez‐Garzón, Patricia; Davidsen, Jörn; Malin, Peter; Karjalainen, Aino; Bohnhoff, Marco; Dresen, Georg
Abstract: We investigate induced seismicity associated with a hydraulic stimulation campaign performed in 2020 in the 5.8 km deep geothermal OTN‐2 well near Helsinki, Finland as part of the St1 Deep Heat project. A total of 2, 875 m 3 of fresh water was injected during 16 days at well‐head pressures <70 MPa and with flow rates between 400 and 1, 000 L/min. The seismicity was monitored using a high‐resolution seismic network composed of 10 borehole geophones surrounding the project site and a borehole array of 10 geophones located in adjacent OTN‐3 well. A total of 6, 121 induced earthquakes with local magnitudes M L H e l > − 1.9 ${M}_{L}^{Hel} > -1.9$ were recorded during and after the stimulation campaign. The analyzed statistical parameters include magnitude‐frequency b ‐value, interevent time and interevent time ratio, as well as magnitude correlations. We find that the b ‐value remained stationary for the entire injection period suggesting limited stress build‐up or limited fracture network coalescence in the reservoir. The seismicity during the stimulation neither shows signatures of magnitude correlations, nor temporal clustering or anticlustering beyond those arising from varying injection rates. The interevent time statistics are characterized by a Poissonian time‐varying distribution. The calculated parameters indicate no earthquake interaction. Focal mechanisms suggest that the injection activated a spatially distributed network of similarly oriented fractures. The seismicity displays stable behavior with no signatures pointing toward a runaway event. The cumulative seismic moment is proportional to the cumulative hydraulic energy and the maximum magnitude is controlled by injection rate. The performed study provides a base for implementation of time‐dependent probabilistic seismic hazard assessment for the project site. Plain Language Summary: We investigate anthropogenic seismicity associated with fluid injection into the 5.8 km deep geothermal OTN‐2 well near Helsinki, Finland, as a part of St1 Deep Heat Project. A total of 2, 875 m 3 of fresh water was injected during 16 days at well‐head pressures <70 MPa and with flow rates between 400 and 1, 000 L/min. The seismicity was monitored using a seismic network composed of 20 borehole geophones located in Helsinki area and in the OTN‐3 well located close by the injection site. A total of 6, 121 earthquakes indicating fractures of 1–30 m size were recorded during and after stimulation campaign. Using a handful of statistical properties derived from earthquake catalog we found no indication for earthquakes being triggered by other earthquakes. Instead, the earthquake activity rates, as well as the maximum earthquake size stayed proportional to the fluid injection rate. The spatio‐temporal behavior of seismicity and its properties suggest earthquakes occurred not on a single fault, but in a distributed network of similarly oriented fractures, limiting the possibility for occurrence of violent earthquakes. The performed study provides evidence that the induced seismicity due to injection performed within St1 Deep Heat project is stable and allow to constrain seismic hazard. Key Points: Induced seismicity associated with stimulation campaign in a 5.8 km deep geothermal OTN‐2 well passively responds to injection operations Seismicity is a non‐stationary Poisson process with seismicity rate and maximum magnitude modulated by the hydraulic energy input rate Seismicity clusters in space and time in response to fluid injection but no interaction between earthquakes is observed